Analisis Framing Dalam Kasus Penyalahgunaan Kip Kuliah Mahasiswi Universitas Diponegoro Di Media Sosial X Dan Media Online Kompas.Tv - Arfian Suryasuciramdhan; Maya Meliasari; Bernika Meilani Ifada; Muhammad Adnan Faidh (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to identify news about the misuse of KIP Lectures circulating in Indonesian online media through platform X (Twitter). The four stages of Framing Entmant include: Define Problem, Diagnose Cause, Make moral judgment and Treatment recommendation. This research uses Robert N's framing analysis method. Entman with a qualitative approach. The results of the research show that Define Problem in the news is related to government policies in the supervision of students/students who receive KIP Lectures that are not in accordance with regulations and can be said that the recipient has a qualified economic background, Diagnosis cause is shown in the form of an indifferent attitude and lack of responsiveness to the government in response to cases of KIP Lecture abuse, Make moral judgment in the form of affirmation that netizens or netizens are attentive in this program as a form of their contribution to the state, and the treatment recommendation offered is how the government collaborates with the same community - the same as overseeing the implementation of the KIP Lecture program and quickly responding to the response to complaints against fraud/abuse As well as tightening the enforcement of rules and regulations in getting KIP Lecture. Online media is a public space that is considered important as a reference in improving public information literacy, so that the news is expected to be objective and educational.